2013
DOI: 10.4315/0362-028x.jfp-12-436
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aspergillus flavus Isolates as Potential Biocontrol Agents of Aflatoxin Contamination in Crops

Abstract: Aspergillus flavus, a haploid organism found worldwide in a variety of crops, including maize, cottonseed, almond, pistachio, and peanut, causes substantial and recurrent worldwide economic liabilities. This filamentous fungus produces aflatoxins (AFLs) B1 and B2, which are among the most carcinogenic compounds from nature, acutely hepatotoxic and immunosuppressive. Recent efforts to reduce AFL contamination in crops have focused on the use of nonaflatoxigenic A. flavus strains as biological control agents. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In the present study, A. fumigatus and A. awamori showed great in vitro and greenhouse biocontrol potentials against the pathogenic fungi. This finding concurs with the results obtained by Rosada et al [ 50 ] and Cook and Baker [ 7 ]. Rosada et al [ 50 ] identified isolates of A. flavus Link with good biocontrol potential against aflatoxin-producing agents in crops.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, A. fumigatus and A. awamori showed great in vitro and greenhouse biocontrol potentials against the pathogenic fungi. This finding concurs with the results obtained by Rosada et al [ 50 ] and Cook and Baker [ 7 ]. Rosada et al [ 50 ] identified isolates of A. flavus Link with good biocontrol potential against aflatoxin-producing agents in crops.…”
Section: Discussionsupporting
confidence: 94%
“…This finding concurs with the results obtained by Rosada et al [ 50 ] and Cook and Baker [ 7 ]. Rosada et al [ 50 ] identified isolates of A. flavus Link with good biocontrol potential against aflatoxin-producing agents in crops. In the present study, A. fumigatus ranked the second most effective in controlling the rice sheath blight fungal agent in the dual culture and greenhouse methods, and first in the volatile metabolite method.…”
Section: Discussionsupporting
confidence: 94%
“…Aspergillus spp. has been previously reported as potential biocontrol agent (Tiwari et al, 2011;Rosada et al, 2013) and also shown to secrete β-glucosidase (Watanabe et al, 1992;Vaithanomsat et al, 2011) that are beneficial for the wine production . Talaromyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, the inability of isolate 1 to form viable heterokaryons between its genetically complementary nit mutants, and its reduced count of hyphal fusions compared with its HSC counterparts (isolates 4 and 13), led it to be characterized as having an HSI phenotype. Although statistically nonsignificant variations in the number of hyphae anastomoses were observed among HSC isolates 4 and 13 of M. phaseolina , significant variations in the frequency of hyphal anastomosis among HSC isolates of Aspergillus flavus and Fusarium solani have been previously demonstrated (Hawthorne & Rees‐George, ; Rosada et al ., ). In the present study, hyphal anastomosis in HSI isolate 1, under laboratory conditions, was found on average to be about six times less common when compared to HSC isolates 4 and 13.…”
Section: Discussionmentioning
confidence: 97%
“…Lack of complementation between the two complementary nit mutants may mean: (i) their original wild isolates are in different VCGs, or (ii) one or both of their wild isolates are unable to form a heterokaryon in which complementation can occur. Such isolates are designated heterokaryon self‐incompatible (HSI; Rosada et al ., ).…”
Section: Methodsmentioning
confidence: 97%